Use of Dhikr Therapy in Overcoming Anxiety in Adolescent Patients - Rahmah, St.; Al Hidaya, Ardian; Vann, Dara; Dara, Ravi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Anxiety disorders among adolescents have become a growing concern, with increasing cases linked to academic pressure, social expectations, and digital media exposure. Conventional treatments often rely on pharmacological and psychological interventions; however, alternative therapies such as dhikr (Islamic remembrance of God) are gaining attention for their potential psychological benefits. Rooted in Islamic spiritual practices, dhikr therapy is believed to induce a calming effect, promote mindfulness, and enhance emotional regulation. Understanding its effectiveness in alleviating anxiety among adolescents can contribute to integrative mental health approaches. This study aims to evaluate the impact of dhikr therapy on reducing anxiety symptoms in adolescent patients through a structured intervention program. A quasi-experimental research design was employed, involving 60 adolescent patients diagnosed with anxiety disorders. Participants were divided into an intervention group receiving guided dhikr therapy and a control group undergoing standard anxiety management. Anxiety levels were measured using the Generalized Anxiety Disorder Scale (GAD-7) before and after the intervention. Findings indicate a significant reduction in anxiety scores among participants in the dhikr therapy group compared to the control group. The study concludes that dhikr therapy serves as an effective complementary approach in managing adolescent anxiety. Recommendations for integrating dhikr therapy into holistic mental health programs are discussed.